I just wanted to ask: A comparison of user studies of the Citizens Advice Bureau (SHIL) in Israel. (March 2014) - Ravid, Gilad; Bar-Ilan, Judit; Baruchson-Arbib, Shifra; Yaari, Eti; Aharony, Noa; Rafaeli, Sheizaf; Weiss-Blatt, Nirit
Day-to-day information needed by citizens can be sought in a variety of ways. Specifically, we were interested in users of online, citizen rights websites, such as the SHIL site (http://shil.info ). Our results report findings from three parallel data collection efforts. Surveys were undertaken to gain a better understanding of how the SHIL website is used and to compare the information needs and information sources used by SHIL users and potential users unaware of the existence of the website. The surveys were administered to samples from three populations (current users of this site, previous users of the site, and users who filled in an offline questionnaire and were mostly unaware of the existence of the SHIL website). We report several interesting differences between the three groups, and suggest future work on analyzing the site, its users, the content it provides and the needs it serves.